Center Places and Cherokee Towns : Archaeological Perspectives on Native American Architecture and Landscape in the Southern Appalachians - Rodning, Christopher Bernard (Book collections on Project MUSE., 2015)
Examines how architecture and other aspects of the built environment, such as hearths, burials, and earthen mounds, formed center places within the Cherokee cultural landscape In Center Places and Cherokee Towns, Christopher B. Rodning opens a panoramic vista onto protohistoric Cherokee culture. He posits that Cherokee households and towns were anchored within their cultural and natural landscapes by built features that acted as "center places." Rodning investigates the period from just before the first Spanish contact with sixteenth-century Native American chiefdoms in La Florida through the development of formal trade relations between Native American societies and English and French colonial provinces in the American South during the late 1600s and 1700s. Rodning focuses particularly on the Coweeta Creek archaeological site in the upper Little Tennessee Valley in southwestern North Carolina and describes the ways in which elements of the built environment were manifestations of Cherokee senses of place. Drawing on archaeological data, delving into primary documentary sources dating from the eighteenth century, and considering Cherokee myths and legends remembered and recorded during the nineteenth century, Rodning shows how the arrangement of public structures and household dwellings in Cherokee towns both shaped and were shaped by Cherokee culture. Center places at different scales served as points of attachment between Cherokee individuals and their communities as well as between their present and past. Rodning explores the ways in which Cherokee architecture and the built environment were sources of cultural stability in the aftermath of European contact, and how the course of European contact altered the landscape of Cherokee towns in the long run. In this multi-faceted consideration of archaeology, ethnohistory, and recorded oral tradition, Rodning adeptly demonstrates the distinct ways that Cherokee identity was constructed through architecture and other material forms. Center Places and Cherokee Towns will have a broad appeal to students and scholars of southeastern archaeology, anthropology, Native American studies, prehistoric and protohistoric Cherokee culture, landscape archaeology, and ethnohistory.